KOMUNIKASI ANTAR PERSONAL ORANG TUA DENGAN ANAK USIA DINI DALAM MENJAGA INTERAKSI SOSIAL AKIBAT PENGGUNAAN PONSEL - Nur Jamila Putri Sutrisno; Juariyah (MEDIAKOM, 2023)
The part of communication contains a exceptionally important presence in passing on messages and data in existence , counting inside the family circle. Its noteworthiness is evident in keeping up connections between family individuals, particularly in connections between guardians and children. Through effective communication, guardians and children can frame a steady mentality to realize common objectives. Inside the system of this investigate, the most consideration is centered on issues that frequently emerge in communication between guardians and children, with illustrations of circumstances such as when guardians are active working exterior the domestic so that restricted time to communicate or connected ideally with children can ended up an deterrent. This inquire about strategy employments a expressive subjective strategy where the information coming about from interviews with asset people will be examined into actualities with respect to the existing issue. This investigate will talk about communication between parents and children which is interpersonal communication utilizing the circular hypothesis of Charles E. Osgood and Wilbur Schramm. The inquire about comes about can be clarified that parental communication is truly required to preserve social interaction, so giving cell phones from an early age continuously without any guidance from parents makes children reluctant to socialize with their peers. However, some parents also experience several obstacles in maintaining their children's social interactions, such as being busy earning a living. Keyword : Interpersonal Communication ; Social Interaction; Cell Phone